Survival or Prophecy? The Correspondence of Jean Leclercq and Thomas Merton - Plekon, Michael (Cistercian studies quarterly, 2011)
The article reviews the book "Survival or Prophecy? The Correspondence of Jean Leclercq and Thomas Merton," edited Patrick Hart.